Nanotechnology in electrocatalysis for energy - Lavacchi, Alessandro (Nanostructure science and technology, 2025)
This book focuses on nanotechnology in electrocatalysis for energy applications. In particular, the book covers nanostructured electrocatalysts for low temperature fuel cells, low temperature electrolyzers and electrochemical valorization. The function of this book is to provide an introduction to basic principles of electrocatalysis, together with a review of the main classes of materials and electrode architectures. This book will illustrate the basic ideas behind material design and provide an introductory sketch of current research focuses. The easy-to-follow three part book focuses on major formulas, concepts and philosophies. This book is ideal for professionals and researchers interested in the field of electrochemistry, renewable energy and electrocatalysis. Introduction -- A bird’s eye view of energy related electrochemistry -- Electrochemical device for energy conversion and storage -- Factors affecting design -- Carbon based nanomaterials -- Other Support Nanomaterials -- Supported metal nanoparticles -- Shape and structure controlled metal nanoparticles -- Monolayer decorated core shell and hollow nanoparticles -- Molecular complexes in electrocatalysis for energy production and storage -- Concluding Remarks.